การควบคุมหุ่นยนต์เคลื่อนที่ด้วยล้อที่สามารถเคลื่อนที่ได้อย่างอิสระ - มงคล เทียนวิบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
To develop an omni-directional wheeled mobile robot which can move in forward-backward direction, lateral and rotation or combination of these three motion. We develop a parallel control architecture for controlling the robot. The motion of the robot is actuated by four DC servomotors connected to the wheels. Each motor will be controlled by one processor. The central processor will responsible for sending the command to each wheel s local processor. The experiments consist of measuring transient response of each wheels with respect to the different magnitude step functions. The motion error will be investigated from straight-line motion, rotating motion and combination of both straight line and rotating motion. For the 1.5 meter straight-line with speed setting below 0.6 m/s and rotation at fixed position with speed setting below 2.1 rad/sec, the maximum error is 5.4% and 6.6% respectively. The motion in close-trajectory such as square and octagon are also investigated. Most of the errors are effect by theenvironment conditions such as slip. This error can be reduced by incorporate more sensors for detecting environment to improve perceptual acuity which can be the research topics in the future.